Quantification of BOLD fMRI parameters to infer cerebrovascular reactivity of the middle cerebral artery. Issue 5 (27th November 2012) - Mazzetto‐Betti, Kelley C.; Leoni, Renata F.; Pontes‐Neto, Octavio M.; Sturzbecher, Marcio J.; Santos, Antonio C.; Leite, Joao P.; Silva, Afonso C.; de Araujo, Draulio B.
Abstract : Purpose: To quantify the amplitude and temporal aspects of the blood oxygenation level‐dependent (BOLD) response to an auditory stimulus during normocapnia and hypercapnia in healthy subjects in order to establish which BOLD parameters are best suited to infer the cerebrovascular reactivity (CVR) in the middle cerebral artery (MCA) territory. Materials and Methods: Twenty healthy volunteers (mean age: 23.6 ± 3.7 years, 11 women) were subjected to a functional paradigm composed of five epochs of auditory stimulus (3 sec) intercalated by six intervals of rest (21 sec). Two levels of hypercapnia were achieved by a combination of air and CO2 while the end‐tidal CO2 (ETCO2 ) was continually measured. An autoregressive method was applied to analyze four parameters of the BOLD signal: onset‐time, time‐to‐peak, full‐width‐at‐half‐maximum (FWHM), and amplitude. Results: BOLD onset time ( P < 0.001) and full‐width at half‐maximum (FWHM) ( P < 0.05) increased linearly, while BOLD amplitude decreased ( P < 0.001) linearly with increasing levels of hypercapnia. Test–retest for reproducibility in five subjects revealed excellent concordance for onset time and amplitude. Conclusion: The robust linear dependence of BOLD onset time, FWHM, and amplitude to hypercapnia suggest future application of this protocol in clinical studies aimed at evaluating CVR of the MCA territory. J. Magn. Reson. Imaging 2013;38:1203–1209. © 2012 Wiley Periodicals, Inc.